2018
DOI: 10.1186/s12894-018-0350-7
|View full text |Cite
|
Sign up to set email alerts
|

With a new clip technique surgically inducing varicocele in Sprague-Dawley rats

Abstract: BackgroundWe introduced and recreated a more consistent and effective experimental varicocele rat model by a new clip technique.MethodsA total of 40 rats were numbered and randomly assigned to 5 groups of 8 each, including sham surgery (Group I), conventional (Group II) and clip groups with 0.7, 0.8, 0.9 mm gap widths, respectively (Group III, IV, V). All of the rats in each group were sacrificed at 8 weeks after initial surgery, and the rats forming out with less than 1 mm diameter of left spermatic vein or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The results of this study showed that the exosome derived from bone marrow mesenchymal stem cells could pass through the blood-testis barrier to the testicular tissue, and it was con rmed by cell experiments that they could be absorbed by spermatogonia. In rat testicular IRI model [28], compared with PBS treatment group and sham operation group after testicular reduction, although exosome derived from bone marrow mesenchymal stem cells could not prevent testicular ischemia-reperfusion injury, it could signi cantly improve the degree of testicular injury and protect the integrity and spermatogenic function of testicular tissue to a great extent through the detection of testicular histomorphology and related oxidative stress indexes. It provides a new idea for preventing ischemia-reperfusion injury after testicular torsion reduction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of this study showed that the exosome derived from bone marrow mesenchymal stem cells could pass through the blood-testis barrier to the testicular tissue, and it was con rmed by cell experiments that they could be absorbed by spermatogonia. In rat testicular IRI model [28], compared with PBS treatment group and sham operation group after testicular reduction, although exosome derived from bone marrow mesenchymal stem cells could not prevent testicular ischemia-reperfusion injury, it could signi cantly improve the degree of testicular injury and protect the integrity and spermatogenic function of testicular tissue to a great extent through the detection of testicular histomorphology and related oxidative stress indexes. It provides a new idea for preventing ischemia-reperfusion injury after testicular torsion reduction.…”
Section: Discussionmentioning
confidence: 98%
“…The incision was primarily closed with a 4/0 silk suture. After 4 hours, by using the same incision line, testis was counter rotated to the natural position and reinserted into the scrotum to induce reperfusion for 2 hours [28].After that ,the two groups ,experimental and Treated group, were respectively injected from the tail vein with the same amount of saline and 100ug/ml exosomes. At the end of the reperfusion period rats were decapitated and testis tissues were taken for biochemical analyses and histological evaluations.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Some studies have reported that varicocele causes a decrease in testicular weight and volume (Guo et al., 2018; Lipshultz & Corriere, 1977), while in others it does not affect (Bitkin et al., 2019; Zhang et al., 2018). In the present study, although testicular weight decreased significantly in the V group compared with the other groups, there was no significant difference between the groups in terms of testicular volume.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were housed in a climate-controlled environment with free access to food and water under a 12-h day/night cycle. Experimental rat varicocele model was constructed according to our new clip technique [13]. The establishment and assessment of the rat model is described in the previous articles published by our team.…”
Section: The Establishment and Assessment Of The Experimental Rat Varmentioning
confidence: 99%